2016
DOI: 10.1259/dmfr.20150424
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of ultrashort echo time MRI sequences for medical additive manufacturing

Abstract: Objectives: Additively manufactured bone models, implants and drill guides are becoming increasingly popular amongst maxillofacial surgeons and dentists. To date, such constructs are commonly manufactured using CT technology that induces ionizing radiation. Recently, ultrashort echo time (UTE) MRI sequences have been developed that allow radiation-free imaging of facial bones. The aim of the present study was to assess the feasibility of UTE MRI sequences for medical additive manufacturing (AM). Methods: Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Comparisons of the bone versus the printed model (both digitized by using optical or CT scanning) also have been performed. These comparisons yielded similar results, with an average difference in dimensions across the entire outer surface of the bone (relative to the 3D model) of less than 1 mm; however, differences can be as high as 5-6 mm in portions of the model (Table 4) (48,51,52,55).…”
Section: Accuracy Of 3d Printed Model Versus Cadaveric and Surgicallymentioning
confidence: 63%
See 2 more Smart Citations
“…Comparisons of the bone versus the printed model (both digitized by using optical or CT scanning) also have been performed. These comparisons yielded similar results, with an average difference in dimensions across the entire outer surface of the bone (relative to the 3D model) of less than 1 mm; however, differences can be as high as 5-6 mm in portions of the model (Table 4) (48,51,52,55).…”
Section: Accuracy Of 3d Printed Model Versus Cadaveric and Surgicallymentioning
confidence: 63%
“…The basic methodology of comparing cadaveric specimens with 3D printed models (Fig 10) has since been applied to all major 3D printing technologies to assess the accuracy of 3D printing of not only the skull (17,34,35,46,47) but also the mandible (45,46,48), vertebral bodies (49), and pelvis (50) ( Table 3). Comparisons of the bone versus the printed model (both digitized by using optical or CT scanning) also have been performed.…”
Section: Accuracy Of 3d Printed Model Versus Cadaveric and Surgicallymentioning
confidence: 99%
See 1 more Smart Citation
“…When a different metal AM machine is used with the manufacturer's recommended process parameters, the reported error may deviate with a fairly good precision of <0.14 mm, excluding the geometries that are prone to support removal error situated on the z-axis [59]. Table 10 lists accuracy measurement studies [81][82][83][84][85][86][87][88][89][90][91][92] of additively manufactured constructs using various anatomical models, imaging medium and modality, measurement principles, AM technologies, and measurement instruments. Most studies have used CT imaging technology to image a dry skull.…”
Section: Additive Manufacturingmentioning
confidence: 99%
“…Several studies have compared the accuracy of CT versus MRI for creation of models, with somewhat mixed results. While some authors concluded that CT‐ and MRI‐derived models are sufficiently comparable in accuracy to warrant the use of MRI data over CT (<1 mm difference between CT and MRI), others reported a >2 mm discrepancy of MRI‐derived models, which they concluded made MRI inappropriate for their clinical use (patient‐specific templates for total knee arthroplasty) . It should be noted that the majority of studies to date assessing relative accuracy of CT versus MRI were performed on cadaveric bone models; since cortical bone does not generate much MRI signal due to extremely short transverse relaxation times ( T 2 ), it is not surprising that MRI performed slightly worse in terms of accuracy when compared to CT. Further, differences in MRI acquisition parameters, segmentation technique, and method of accuracy assessment (eg, computer‐based model comparison vs. physical measurement with calipers) all make the current body of work challenging to apply broadly.…”
Section: Accuracy Of Mri‐based Modelsmentioning
confidence: 99%